Central Bank Policy of Great Britain, Expressed in the Strategy of Direct Inflation Targeting - Lechowicz, Tomasz (Journal of Finance and Financial Law, 2015)
The aim of the study is to analyze the inflation targeting strategy used in the UK as a tool of monetary policy. Shown are the main advantages and disadvantages of this strategy. Presented answer to the question about the effectiveness of direct inflation targeting strategy for the economy. The time period covers the years 2001–2014.